Implementation of Intergenerational Practices for Promoting Active Aging - Mercieca, Ilona (Magyar Gerontológia, 2024)
Ageing is a complex, natural process which encompasses a cascade of biological, psychological and social changes occurring in an individual’s lifespan. Its phenomenal experience is influenced by a myriad of factors, including genetics, environment, lifestyle and socio-economical aspects.